La importancia de la gestión financiera en la empresa Red Acces S.A. - Cuamacas Granizo, Renato David (Machala : Universidad Técnica de Machala, 2022)
The company RED ACCESS, which is dedicated to the sale of different internet services, technical service and equipment maintenance, has found the following problem in the company: the deficient and non-optimal application of financial management, which implies that the management of resources is not adequate, that is why I have carried out this project as a theme: IMPORTANCE OF FINANCIAL MANAGEMENT IN THE COMPANY RED ACCESS S.A. whose general objective is to analyze the importance of the correct use of financial management in the company, describes the main financial strategies used by the company RED ACCESS S.A. The present investigation, for the full fulfillment of the proposed objectives, will have a non-experimental cross-sectional design (Herbas and Rocha, 2018), in the sense that the different variables that are typical of the financial information of the company will not be deliberately manipulated. company RED ACCESS S.A. of the last two years (2020-2021), with the clear purpose of observing and analyzing their natural environment, to subsequently describe them in a precise and orderly manner and thus measure how they have limited financial management. One of the main conditions within the function of finance, and which plays a very important role when establishing proper financial management, is that all areas of responsibility of the company maintain constant interaction with the personnel and the a priori and a posteriori needs that may arise in the daily activity of the organization. For this, finance professionals have to anticipate the needs through forecasting methods that organizations need to satisfy, and thus make the best decisions when establishing strategies. It should be noted that the management of finances maintains a close relationship with economic and accounting aspects. According to what the different previously mentioned authors dissert, financial management has a fundamental and leading role when carrying out the different business activities, whether in small, medium or large-sized for-profit organizations. At the same time, it is argued that financial management gives its benefactor more information on the economic and accounting aspects of the company, in order to organize all the resources available, in order to make better decisions at the time. to establish strategies to increase profitability.In view of the results obtained, the main recommendation that the RED ACCESS company is urged to improve its strategies when managing its assets and debts, since it has been shown that the largest amount of its capital is financed by third parties (debt). In the same way, you must implement tools that allow you to control how your different assets are being used, in order to favor the rotation of investments, and therefore their volume of profitability for subsequent years.
La empresa RED ACCESS que se dedica a la venta de diferentes servicios de internet, servicio técnico y mantenimiento de equipo, en la empresa se ha encontrado la siguiente problemática: la aplicación deficitaria y no óptima de la gestión financiera, lo que implica que el manejo de los recursos no sea adecuado, es por ello que he realizado este este proyecto como tema: IMPORTANCIA DE LA GESTIÓN FINANCIERA EN LA EMPRESA RED ACCESS S.A. que tiene como objetivo general Analizar la importancia del correcto uso de la gestión financiera en la empresa, describe las principales estrategias financieras que utiliza la empresa RED ACCESS S.A. La presente investigación para el cumplimiento cabal de los objetivos planteados, tendrá un diseño no experimental de tipo transversal (Herbas y Rocha, 2018), en el sentido que no se manipularán de manera deliberada las diferentes variables que son propias de la información financiera de la empresa RED ACCESS S.A. de los últimos dos años (2020-2021), con el claro propósito de observar y analizar su entorno natural, para a posteriori describirlas de forma precisa y ordenada y así medir como han acotado dentro de la gestión financiera. Una de las principales condicionantes que se tiene dentro de la función de las finanzas, y la cual, juega un rol de suma importancia a la hora de entablar una correcta gestión financiera es que, todas las áreas de responsabilidad de la empresa mantengan una constante interacción con el personal y las necesidades a priori y a posteriori que se puedan presentar en la actividad cotidiana de la organización. Para esto, los profesionales de las finanzas tienen que prever las necesidades a través de métodos de pronósticos que las organizaciones requieren satisfacer, y así tomar las mejores decisiones a la hora de establecer estrategias. Cabe señalar que la gestión de las finanzas mantiene una estrecha relación con los aspectos económicos y contables. De acuerdo a lo que disertan los diferentes autores previamente citados, la gestión financiera tiene un rol fundamental y protagónico a la hora de llevar a cabo las diferentes actividades empresariales, ya sea, en organizaciones con fines de lucro de pequeño, mediano o grande tamaño. A su vez, se diserta que, la gestión financiera otorga a su benefactor mayor información sobre los aspectos económicos y contables propios de la empresa, con la finalidad de organizar todos los recursos con los que se cuenta, para así tomar mejores decisiones a la hora de establecer estrategias que permitan aumentar la rentabilidad. En vista de los resultados obtenidos, la principal recomendación que se exhorta a la empresa RED ACCESS, es que mejore sus estrategias a la hora de manejar sus activos y deudas, puesto que, se ha evidenciado que la mayor cantidad de su capital es financiado por terceros (deuda). De la misma manera, debe implementar herramientas que le permita el control de cómo se están utilizando sus diferentes activos, para así favorecer la rotación de inversiones, y por ende su volumen de rentabilidad para los años posteriores.
Keywords: ADMINISTRACION; EMPRESA; GESTION FINANCIERA; CAPITAL